The A Multimodal Approach to Language Learning: The Role of Puragabaya Music and Poetry Video - Widara Putra, Adita; Rosiana, Shinta; Kartadireja, Welly Nores; Nurjamilah, Ai Siti; Suriani, Siti (Faculty of Teacher Training and Education Muhammadiyah University of Makassar, 2026)
Objective: This study explored the integration of multimodal texts in language learning within the Merdeka Belajar curriculum framework, which emphasizes four core competencies aligned with the 21st-century educational goals. Method: Using Arts-Based Educational Research (ABER) with the Art in Research approach, we developed a music and poetry video depicting the Puragabaya Legend from Galunggung, Tasikmalaya as an innovative digital teaching material. Result: The creative process successfully produced digital performance that meets both aesthetic and educational requirements. The Puragabaya Music and Poetry Video demonstrates an effective integration of verbal metafunctions (narrative structure and cultural storytelling) and visual metafunctions (symbolic imagery and representational elements) that enhance students' comprehension and cultural understanding. The video effectively bridges traditional storytelling with contemporary digital literacy demands, providing concrete examples of metaphorical language use within authentic cultural contexts. Novelty: This research contributes to educational innovation by demonstrating how arts-based digital materials can serve both pedagogical and aesthetic functions, offering a replicable model for integrating local cultural content into language learning curricula through creative multimedia production.